Dampak Wabah COVID-19 Terhadap Pelayanan Perpustakaan di Indonesia - Kusmayati, Deti; Radiana, Usman; Kamariyah, Syarifah; Simalun, Emilia (Jurnal Pendidikan Indonesia, 2022)
The Corona Virus outbreak entered Indonesia in early March 2020. This COVID-19 pandemic has had many impacts on several services in Indonesia, including library services. In the world of education, the library is a source of information that is widely chosen to obtain literature. This study uses a descriptive method of literature study. The object of this research is articles, scientific journals and books related to the problems faced in library services. Large-Scale Social Restrictions (PSBB) from the government, namely staying at home to reduce the transmission rate of COVID-19 in Indonesia. The public began to seek information through the internet. This journal aims to explain the impact of the COVID-19 outbreak on library services in Indonesia, the corona mass has become a magnifying glass that has helped someone to critically look for ways so that they can still get information. Since March 2020 there have been many moments of evaluation and reflection, both online and limited face-to-face, this insight provides ideas about the impact of the COVID-19 outbreak on library services in Indonesia.